Comorbidities, risk factors and maternal/perinatal outcomes in oocyte donation pregnancies. Issue 2 (August 2020) - Rizzello, Francesca; Coccia, Maria Elisabetta; Fatini, Cinzia; Badolato, Laura; Fantappiè, Giulia; Merrino, Valeria; Petraglia, Felice
Abstract: Research question: To evaluate pre-existing comorbidities, obstetric risk factors and adverse obstetric and neonatal outcomes in pregnancies conceived by oocyte donation, compared with naturally conceived pregnancies or by conventional IVF/intracytoplasmic sperm injection (IVF/ICSI). Design: This retrospective single-centre contemporary cohort study reviewed data from singleton deliveries at the University Hospital of Careggi, Florence, from 2009 to 2017. Maternal and perinatal outcomes were analysed. Results: The study included 25, 851 pregnancies and newborns: 276 (1.1%) children were conceived after oocyte donation, 925 (3.6%) after IVF/ICSI and 24, 650 (95.4%) after natural conception. Women in the oocyte donation group were significantly older compared with IVF/ICSI and natural conception groups ( P  < 0.0001) and had a higher prevalence of chronic hypertension compared with the natural conception group ( P  = 0.0090). They were administered anticoagulant medications more frequently during pregnancy. The incidence of gestational hypertension was significantly higher than in natural conception (aOR 3.6) and IVF/ICSI pregnancies (aOR 2.7). The incidence of Caesarean section in oocyte donation pregnancies was higher than in natural conception and IVF/ICSI groups (aOR 3.4 and 2.3, respectively). An 11-fold increased risk of post-partum haemorrhage (PPH) was found in oocyte donation versus natural conception and an almost four-fold increased risk was found in oocyte donation versus IVF/ICSI; prematurity and low birthweight were more frequent after oocyte donation versus natural conception (aOR 2.4 and 1.8, respectively). Conclusions: Patients undergoing oocyte donation represent a group with increased comorbidities and risk factors for adverse obstetric outcomes. Oocyte donation seems to be independently associated with gestational hypertension and PPH. Pregnancies after oocyte donation warrant clinical surveillance with proper screening and, possibly, preventive strategies.